The 1941 June Uprising in Pušalotas Rural Area of Panevėžys County - Jaskelevičius , Tadas (Genocidas ir rezistencija, 2015)
The 1941 June uprising in Pušalotas rural area of Panevėžys County was the acme of the anti-Soviet resistance that had been taking place at the time. The main reason for the participation of the population of Pušalotas rural area in the 1941 June uprising was their patriotism: like many people in Lithuania, the rebels were convinced that the Germans will free Lithuania from the Soviets and the country will regain its independence. Preparations for the uprising in Pušalotas rural area were made in advance. Since the start of the Soviet occupation, future rebels amassed arms and ammunition. Partisans began their operations on the second day of the war between Germany and the USR . In stage one (in the first days) of the uprising, squads of rebels were formed in various locations of the rural area. Later they merged into one large unit with the command in the town of Pušalotas (from the very beginning of the uprising there was only one rebel command in Pušalotas rural area). During the uprising, the partisans sought their main goal to restore the independence of Lithuania. As a result, they actively fought against the Red Army troops retrieving across Pušalotas rural area and arrested local Soviet activists.The characteristic feature of the 1941 June uprising in Pušalotas rural area was that it was very erratic: initially, the rebels quickly took the power into their hands, but were soon forced out by Red Army forces which outnumbered the rebels, and later again managed to regain control over the area. During the combat with the Red Army troops, NKVD personnel, militia men and Soviet activists, two rebels were killed; at least eight lives were lost on the Soviet side. At least 28 civilians were arrested on suspicion that they were Soviet activists. If suspicions were not confirmed, those persons were released. Based on the archival sources, it was not established that any civilian had been shot in Pušalotas rural area during the uprising.During the uprising, on 23–26 June 1941, the Jews of Pušalotas were not massively persecuted. There were instances of individual persecution. During the uprising, the rebels detained six Jews. At least one of them was executed in July 1941, the fate of the remaining five people is not known, but it is likely that they may have been executed in July–August 1941. The archival sources indicate that the main reason for the persecution of the Jews during the uprising was the suspicion that they were Soviet activists.At least 96 people and another 90 local residents could have taken part in the uprising in Pušalotas rural area, but there is no archival data to confirm or deny this.
Keywords: soviet occupation; antisoviet resistance; uprising